2005
DOI: 10.1007/s00455-005-0021-1
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Stimulation with Air-Pulse Trains Increases Swallowing Frequency in Healthy Adults

Abstract: This study sought to determine whether air-pulse trains delivered to the peritonsillar area would facilitate swallowing in healthy subjects. Trains of unilateral or bilateral air pulses were delivered to the peritonsillar area via tubing embedded in a dental splint, while swallows were simultaneously identified from their associated laryngeal and respiratory movements. Results from four subjects indicated that oropharyngeal air-pulse stimulation evoked an irrepressible urge to swallow, followed by an overt swa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 35 publications
(54 reference statements)
5
35
0
Order By: Relevance
“…The present finding that saliva swallowing is facilitated by oropharyngeal air-pulse stimulation in older adults is consistent with our earlier report that oropharyngeal airpulse application increases saliva swallowing in younger adults [1], a finding recently corroborated by Lowell et al [2]. Taken together, these studies indicate that both young and older adults show increased saliva swallowing rates in response to oropharyngeal air-pulse stimulation.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The present finding that saliva swallowing is facilitated by oropharyngeal air-pulse stimulation in older adults is consistent with our earlier report that oropharyngeal airpulse application increases saliva swallowing in younger adults [1], a finding recently corroborated by Lowell et al [2]. Taken together, these studies indicate that both young and older adults show increased saliva swallowing rates in response to oropharyngeal air-pulse stimulation.…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings have recently been reported by Lowell et al [2]. We also showed that bilateral oropharyngeal air-pulse stimulation tended to be associated with a higher mean saliva swallowing rate and shorter mean swallowing latency compared with unilateral oropharyngeal air-pulse stimulation [1], suggesting a possible role for spatial summation in the facilitatory effect of air pulses on swallowing.…”
supporting
confidence: 78%
See 3 more Smart Citations